2022
DOI: 10.3390/curroncol29020040
|View full text |Cite
|
Sign up to set email alerts
|

Models of Follow-Up Care and Secondary Prevention Measures for Survivors of Colorectal Cancer: Evidence-Based Guidelines and Systematic Review

Abstract: Objective: To provide recommendations for preferred models of follow-up care for stage I-IV colorectal (CRC) cancer survivors in Ontario; to identify signs and symptoms of potential recurrence and when to investigate; and to evaluate patient information and support needs during the post-treatment survivorship period. Methods: Consistent with the Program in Evidence-Based Medicine’s standardized approach, MEDLINE, EMBASE, PubMed, Cochrane Library, and PROSPERO databases were systematically searched. The authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A recent systematic review and synthesis of qualitative evidence showed that information needs, interaction with health care professionals and support to cope and adjust to survivorship were crucial [36]. This was supported by another systematic review which also emphasised the importance of self-management instructions and clear patient information about when and how to contact healthcare professionals [37]. Self-management strategies require that patients act proactively and that clear options for self-management and support are available [38,39].…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…A recent systematic review and synthesis of qualitative evidence showed that information needs, interaction with health care professionals and support to cope and adjust to survivorship were crucial [36]. This was supported by another systematic review which also emphasised the importance of self-management instructions and clear patient information about when and how to contact healthcare professionals [37]. Self-management strategies require that patients act proactively and that clear options for self-management and support are available [38,39].…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…Myth: Shared Care Results in the Best Outcomes for Cancer Survivors Shared care is a term that describes deliberate efforts to coordinate components of survivorship care between specialty and primary care providers (PCPs), practice settings, or electronic health records (EHRs). Multiple reports and manuscripts recommend shared care as the preferred model for survivorship care, [5][6][7] starting with the Lost in Transition report calling for coordination between specialists and PCPs. 8 However, available data challenge the belief that shared care is superior to PCP or oncology-led care in several ways.…”
Section: Introductionmentioning
confidence: 99%